Students' thinking paths The Open Educational College (Journal of the College of Basic Education, 2022)
Mathematics students consider that learning this subject is not limited to knowing and understanding the content of its topics, but rather that it contributes directly or indirectly to all fields of knowledge, as well as its contribution to the development of human thought, because it is not limited to the applied side, but rather it is (a method And a pattern in thinking, organizing logical proof, and determining the percentage of the possibility of the validity of a hypothesis or a case (Abu Zeina 1997, p. 18). Therefore, theorists of mathematics and its teaching methods counted.